(untitled) (Research, Society and Development, 2024)
The objective of this manuscript is to present a sustainable alternative for the use of waste from Water Treatment Plants (WTPs), specifically water treatment sludge (WCS), in civil construction. The proposal is to use water treatment sludge as a construction material, more specifically in the partial replacement of cement in self-compacting mortars (SCC). Due to the significant use of natural resources in civil construction and the consequent environmental degradation, the use of water treatment sludge (WCS) as a construction material may be an option. However, the low quality of river water and the need for drinking water force water treatment plants to use greater quantities of chemical compounds, resulting in a significant waste known as WCS. The methodology used for dosing self-compacting concrete (SCC) follows the process described by the Gomes method, which is applicable to both concrete and self-compacting mortars. In this study, the partial replacement of cement at 2.5% and 10% with water clarification mud (WCS) in self-compacting mortars (SCC) was analyzed and it was found that the compressive strength increased from 27.3% to 30% for the specimens, with the addition of 2.5% and 10% of WCS, respectively. A life cycle assessment was carried out to prove the environmental benefits of replacing cement with WCS. The results preserve the feasibility of applying WCS in civil construction while at the same time highlighting the need for additional research on the topic.